Kinetic analysis of crouching start depending on taping applied to hamstring in elite male sprinters - Kim, T.; Park, J. C.; Park, J. M.; Choi, H. (The Korean Journal of Sports Medicine, 2021)
Purpose: This study was aimed to identify the effect of taping applied to both hamstring on the horizontal velocity of the center of mass (COM) and the angle and peak angular velocity of the knee and hip joints in the sagittal plane during the crouching start.